Nonalcoholic Fatty Liver Disease: Pathogenesis and Treatment in Traditional Chinese Medicine and Western Medicine - Shi, Tingting (Evid Based Complement Alternat Med, 2020)
Nonalcoholic Fatty Liver Disease (NAFLD) is one of the most important causes of liver disease worldwide and probably destined to become the leading cause of end-stage liver disease in the coming decades, affecting both adults and children. Faced with the severe challenges for the prevention and control of NAFLD, this article discusses the understanding and mechanism of NAFLD from Chinese and Western medicine. Moreover, the progress regarding its treatment in both Chinese and Western medicine is also summarized. Both Chinese medicine and Western medicine have their own characteristics and clinical efficacy advantages in treating diseases. The purpose of this article is to hope that Chinese and Western medicine have complementary advantages, complementing each other to improve clinical NAFLD therapy prevention and treatment methods to receive more and more attention throughout the global medical community.